The multipurpose use of industrial wastes in the process of producing anhydrite construction materials; IFOST 2012; Vol. 1 - Fedorchuk Yu. M. Yuri Mitrofanovich (Section 1. Chemical engineering and "Green technology", 2012)
The article presents officially accepted way of involving factory wastes from chemical industry (acid fluorides, carbidic silt), transport industry (used accumulator lead-zinc electrolytes and nickel-cadmium electrolytes) and heat and power industry (ash) in the cycle of shared consumption with the Tomsk region taken as an example. In this case there is reduction of environmental impact and production ofcost-effective, competitive and popular construction materials and products.